If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-1x/12=10/12
We move all terms to the left:
-1x/12-(10/12)=0
We add all the numbers together, and all the variables
-1x/12-(+10/12)=0
We get rid of parentheses
-1x/12-10/12=0
We multiply all the terms by the denominator
-1x-10=0
We move all terms containing x to the left, all other terms to the right
-x=10
x=10/-1
x=-10
| 2x²+12x=-18 | | M+3^2=m-5 | | 60=-6b+4b | | (y/4)-3=5 | | 5x-8=10x-7 | | 9v+6-3v=-18 | | 1.04x-x=15 | | 98-2x^=0 | | a-4.5=8.1 | | (y/2)-6=3 | | 1/5d-5=2 | | (y/5)-2=5 | | 6(2y+4)=72 | | x-16(-8-2x)=-128 | | 7x/3-1/2=3 | | -3r+13r=-120 | | 1.84g-11=96 | | 1x^2+2.4x+1.44=0 | | .1x-42579=x | | 12p-10=2612p-10=26 | | .1x+42579=x | | -24x+15=-81 | | .1x+42579=38708 | | 10/2a=20/4 | | 17=8x+ | | 2x+4x+6=90 | | x=12=8 | | x=23=-17 | | 13+2a=2a-3 | | 0.2x+5=0.4-12 | | 4=r+5+3 | | (y/8)-4=2 |